The Effect of Diabetes Mellitus on the Thickness of Gingival Junctional Epithelium (Study in the Experiment of Caspase-3) - Abdelaziz Eljawadi; Totok Utoro; Nunuk Purwanti (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2012)
Diabetes mellitus (DM) is a metabolic disorder manifested by abnormally high levels of blood glucose, resulting in hyperglycemia that affects the oral cavity, leading to periodontitis. The junctional epithelium (JE) is the epithelial component of the dento-gingival unit that is in contact with the toothsurface. Apoptosis and proliferation of JE are essential to maintenance JE thickness. Apoptosis is programmed cell death that can be triggered by various signals and is characterized by well-defined morphologic changes and biochemical features. Caspase-3 is involved in the underlying mechanisms of apoptosis, and the activation of caspase-3 is considered to be the final step in many apoptosis pathways. Purpose of this study was to investigate the effect of DM on the expression of caspase-3 and the thickness of JE. Sixteen male Sprague-Dawley rats were used and divided equally into two groups: the diabetic group that injected intraperitoneal by streptozotocin (STZ) and negative control group. Measurements of blood glucose levels were analyzed before and at 2, 4 weeks after STZ injection. In addition, JE thickness and expression of caspase-3 were examined after 2 and 4 weeks. JE was stained by hematoxylin-eosin (H&E) staining for thickness measurement and the immunohistochemistry by using the anti-caspase-3 antibody for caspase-3 expression measurement and examined under light microscope. The results of the present study showed that a decrease of JE thickness and increase of caspase-3 expression were obtained while increasing the diabetic duration. Two ways Anova and Least Significant Difference (LSD) tests indicated a significant difference of JE thickness and caspase-3 expression between all groups except in diabetic group after 2 and 4 weeks. Also, caspase-3 expression in diabetic group after 2 and 4 weeks (P > 0.05) were not significantly different. It can be concluded that diabetes mellitus (DM) affected on the thickness and caspase-3 expression of JE. Furthermore, the results suggest that high expression of caspase-3 was associated with the diabetes-induced apoptotic cell-death resulting in reduction of JE thickness.